The Effect of Consumer Satifitation and Product Quality on Purchase Decisions On Tiktok Live Shopping - Fitria Nugraheni; Putri Aprilla Rani; Dori Fansir (Prosiding International conference on Information Technology and Business (ICITB), 2022)
In online shop marketing, there are several online media that are often used, such as tiktok live shopping. The buying decision process includes several stages of information seeking, comparing alternatives, decision making, and post-purchase behavior. This study aims to determine whether consumer satisfaction and product quality have a significant influence on purchasing decisions on live shopping tiktok. The type of research used in this research is causal associative research. Data was collected using a questionnaire with a total of 30 respondents. In the research results, there are measurements that can be distributed to determine whether there is an influence of Consumer Satisfaction (X1) and Product Quality (X2) on Purchase Decisions (Y) on Tiktok Live Shopping, by processing the data obtained through questionnaires that have been filled out by respondents to find out the results of testing the hypothesis.Keywords: Consumer Satisfation, Product Quality, and Purchase Decision